Serrin-Type Overdetermined Problem in $\mathbb H^n$ (Journal of Partial Differential Equations, 2023)
In this paper, we prove the symmetry of the solution to overdetermined problem for the equation $σ_k(D^2u-uI)=C_n^k$ in hyperbolic space. Our approach is based on establishing a Rellich-Pohozaev type identity and using a $P$ function. Our result generalizes the overdetermined problem for Hessian equation in Euclidean space.